Power-combining based on master-slave injection-locking magnetron - 袁萍 张益 叶文军 朱铧丞 黄卡玛 杨阳 (Chinese physics B, 2016)
A microwave power-combining system composed of two Panasonic 2M244-M1 magnetrons based on master–slave injection-locking is demonstrated in this paper. The principle of master–slave injection-locking and the locking condition are theoretical analyzed. Experimental results are consistent with the theoretical analysis and the experimental combined efficiency is higher than 96%. Compared with the external-injection-locked system, the power-combining based on the master–slave injection-locking magnetron is superior by taking out the external solid-state driver and the real-time phase control system. Thus, this power-combining system has great potential for obtaining a high efficiency, high stability, low cost, and high power microwave source.